(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In this 21stcentury we have been encountering various kinds of problems. The issue of Streetchildren is one of them: a vulnerable section of society. Thesechildren are commonly seen when we stop near traffic signals and when theyapproach people with different needs, some for begging and some for sellingtheir prepared items.